MIGRASI DAN KESEJAHTERAAN RUMAH TANGGA PETANI - Rani Andriani Budi Kusumo; Gema Wibawa Mukti; Anne Charina (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Farmer’s households often carry out migration activities as a form of livelihood strategy. The remittances generated are expected to impact improving the welfare of farmer households. This study aimed to analyze changes in the welfare of farmer households due to the migration carried out. This study uses panel data from the Indonesia Family Life Survey (IFLS) wave 4 (in 2007) and wave 5 (in 2014). The unit of analysis of this study is a farmer’s household in West Java Province, whose one or all of their family members migrated between 2007-2014. Data were analyzed using descriptive statistics to see changes in welfare levels before and after migration. The results showed that the migration carried out by farmers impacted changes in the level of welfare both objectively and subjectively. The increase in asset ownership and respondents' perceptions of welfare indicators tend to be higher after they migrate. Assistance to migrant households needs to be carried out so that the remittances produced can be used optimally to improve household welfare.